2015
DOI: 10.1039/c5tb00312a
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Au@Pt@Au core–shell nanoparticles on graphene oxide nanosheets for high-performance H2O2bi-directional sensing

Abstract: Bimetallic Au@Pt@Au triple-layered core-shell nanoparticles consisting of a Au core, Pt inner shell, and an outer shell composed of Au protuberances on graphene oxide (GO) nanosheets were successfully prepared by a galvanic replacement and reagent reduction reaction. Scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), energy dispersive X-ray spectroscopy (EDX), inductively coupled plasma-atomic emission spectroscopy (ICP-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 54 publications
0
33
0
Order By: Relevance
“…In light of these findings and the unique properties of bimetallic NPs, a number of potential applications still remain to be explored that exploit the enzyme-mimicking functions of alloy NPs. For example, AuPt bimetallic nanostructures have exhibited intrinsic multiple enzyme-like activities, but most of these works involved AuPt bimetallic nanostructures rather than AuPt alloy nanoparticles92224293031. The study on AuPt alloy nanoparticles for tailoring their chemical compositions to fine tune the oxidase and peroxidase-like activity and sensing capability for biodetection are limited.…”
mentioning
confidence: 99%
“…In light of these findings and the unique properties of bimetallic NPs, a number of potential applications still remain to be explored that exploit the enzyme-mimicking functions of alloy NPs. For example, AuPt bimetallic nanostructures have exhibited intrinsic multiple enzyme-like activities, but most of these works involved AuPt bimetallic nanostructures rather than AuPt alloy nanoparticles92224293031. The study on AuPt alloy nanoparticles for tailoring their chemical compositions to fine tune the oxidase and peroxidase-like activity and sensing capability for biodetection are limited.…”
mentioning
confidence: 99%
“…Che et al [ 57 ] commented on the synergism between Au and Pt as contributing to an improvement in the analytical performance when compared to an electrode modified with Au NPs or Pt NPs alone. Interestingly the seven most recent papers, all third generation sensors using non-enzymatic, mediator-free approaches—namely, those by Li et al [ 48 ], Kung et al [ 49 ], Hwang et al [ 50 ], Lu et al [ 51 ], Janyasupab et al [ 52 ] and Chen et al [ 53 ] have shown a convergence in approach with respect to both the nature of the constructs employed, i.e. , all containing Pt, and using carbon, in various forms, as a support material.…”
Section: Biosensors—grouped By Target Analytementioning
confidence: 99%
“…Active radicals produced by H 2 O 2 degradation are believed to be extremely short lived. Nanoparticles possesses peroxidase‐like activity which have a high affinity for H 2 O 2 , and the combination of RGO and cobalt generates a synergistic effect that increases the peroxidase‐like activity of graphene materials . In this work, we synthesized cobalt‐tetraphenylporphyrin (CoTPP) molecules and assembled them on an RGO surface.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles possesses peroxidase-like activity which have a high affinity for H 2 O 2 , and the combination of RGO and cobalt generates a synergistic effect that increases the peroxidase-like activity of graphene materials. [28][29][30][31][32][33][34][35] In this work, we synthesized cobalt-tetraphenylporphyrin (CoTPP) molecules and assembled them on an RGO surface. The CoTPP/RGO nanocomposite was exposed to active radicals for longer than was CoTPP.…”
Section: Introductionmentioning
confidence: 99%